Ullmann's Encyclopedia of Industrial Chemistry 2007
DOI: 10.1002/14356007.a01_149.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein and Methacrolein

Abstract: The article contains sections titled: 1. Introduction 2. Properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 78 publications
0
44
0
2
Order By: Relevance
“…66 Studies of copper oxides in a flow reactor for this transformation indicate competing combustion, particularly when the catalyst was oxidized before use. 67,68 Even without pre-oxidation, a ratio of ~52:44 acrolein:CO 2 was observed, with small amounts of acetaldehyde and propionaldehyde also detected.…”
Section: Reactions Of Hydrocarbonsmentioning
confidence: 99%
“…66 Studies of copper oxides in a flow reactor for this transformation indicate competing combustion, particularly when the catalyst was oxidized before use. 67,68 Even without pre-oxidation, a ratio of ~52:44 acrolein:CO 2 was observed, with small amounts of acetaldehyde and propionaldehyde also detected.…”
Section: Reactions Of Hydrocarbonsmentioning
confidence: 99%
“…Symptoms of exposure to acetaldehyde include nausea, vomiting, and headache. Acrolein, an unsaturated carbonyl, is an eye irritant and exacerbates asthma (Arntz et al, 2012). Feng et al (2006) demonstrated that the lung cancer risk was elevated from inhalation of acrolein emitted from ETS.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst lifetime can be over a dozen years for acrolein production, or shorter when the targeted product is acrylic acid. Indeed, in that It has been produced in the past by the condensation of formaldehyde and acetaldehyde [1,5] (Reaction A, Scheme 1). More recently, there has been a lot of interest in the conversion of glycerol, a co-product of biodiesel and oleochemistry, through double intramolecular dehydration [6] (Reaction C, Scheme 1).…”
Section: Curent Route From Fossil Resources: Propylenementioning
confidence: 99%
“…Acrolein, also known as propenaldehyde, is a synthetic chemical currently produced by propylene selective oxidation (Reaction B, Scheme 1). It is used for the production of fine chemicals such flavor and fragrances and pharmaceutical compounds, including antibiotics and antimicrobials [1][2][3][4]. It is also used in larger quantities to produce methionine (an essential amino acid), and as a non-isolated intermediate to acrylic acid.…”
Section: Introductionmentioning
confidence: 99%